The infinite scroll … exploring the motivations and individual differences in binge-watching behavior on porn tube sites - Shilpa Kalyan; Devadas Menon; Saravanan Velakutty Mariyappan (Social Sciences and Humanities Open)
What are the motivations for binge-watching porn tube sites? To what extent do sensation seeking and the need for cognition have moderating effects? This study investigates these pertinent questions through the theoretical framework of uses and gratification. The Study delves into five motivations for binge-watching behaviour: Excitement seeking, Diversion, Fantasy, Arousal, and Habitual pastime. The Online Survey conducted across 380 participants in India highlights the significance of these motivations in driving individuals to engage in extensive viewing of adult content on tube sites. Through moderation and regression analysis, the study establishes the causal relationship between individual differences marked by personality traits like sensation seeking and the need for cognition in positively influencing and intensifying binge-watching behaviour. This study, essentially, presents a comprehensive investigation into the motivations behind binge-watching porn tube sites in the Indian demographic framework. It emphasises the interaction between individual differences and the driving forces behind this media consumption behaviour.